Value management of construction projects - Kelly, John.; Male, Steven; Graham, Drummond (Oxford, UK ; Malden, MA : Blackwell Science, 2004)
This book presents an integrated value philosophy, methodology and tool kit for improving project delivery for clients, based on best practice. It combines the theory and practice of value management and is written in such a way that the theory, methodology, workshop styles, tools and techniques can be read independently if the reader wishes.
Preface; Introduction; Definition; Developments in value management; Developments in UK construction; Developments in value management practice; The aims and objectives of this book; References; Part I Method and Practice; Developments in Value Thinking; Introduction; Background; The global development of value management; Value engineering and value management: an overview of terminology and definitions; The international benchmarking study of value management; Conclusion; References; Function Analysis; Introduction; Strategic function analysis: the mission of the projects; Strategies, programmes and projects; Function diagramming; Kaufman's FAST diagramming; Functional space diagramming; Elemental cost planning and elemental cost control; Element function analysis; Element function debated; Conclusion; References; Bibliography; Index
engineering bookfair2015
Includes bibliographical references (p. 363-366) and index.
Keywords: Construction industry -- Management; Value analysis (Cost control); Project management